Kerangka Pengaturan Penanganan Gangguan Ketenteraman, Ketertiban Umum Dan Pelindungan Masyarakat Dalam Satu Daerah Kabupaten/Kota - Ngesti Dwi Prasetyo (Yurispruden: Jurnal Fakultas Hukum Universitas Islam Malang, 2023)
The relationship between decentralization and regional autonomy directs that regional governments are responsible for various aspects of society, one of which is handling disturbances to peace, public order, and community protection. Unfortunately, not all of the laws and regulations in Indonesia can become a reference for local governments because the content material is still empty (rechtvacuum). The research method used is normative juridical with a statutory approach. The results of this study describe that regional regulations regarding handling disturbances to peace, public order and community protection must at least fulfill 3 (three) foundations, namely philosophical, sociological, and juridical. The framework for the direction of content consists of at least 12 chapters which include content including FORKOPIMDA, KID, and mapping of potential areas of disturbance to peace and public order.